2014
DOI: 10.1371/journal.pone.0110443
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Isolation of Extracellular Vesicles from Cell Culture and Biological Fluids Using a Synthetic Peptide with Specific Affinity for Heat Shock Proteins

Abstract: Recent studies indicate that extracellular vesicles are an important source material for many clinical applications, including minimally-invasive disease diagnosis. However, challenges for rapid and simple extracellular vesicle collection have hindered their application. We have developed and validated a novel class of peptides (which we named venceremin, or Vn) that exhibit nucleotide-independent specific affinity for canonical heat shock proteins. The Vn peptides were validated to specifically and efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
155
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 49 publications
2
155
0
Order By: Relevance
“…Nanoparticle tracking analysis (NTA) and electron microscopy (EM) have been performed on Vn96 mediated extracellular vesicle isolations of MCF-10A and MCF-7 cell culture media previously [7,26]. Both studies found particle size distributions consistent with small EVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle tracking analysis (NTA) and electron microscopy (EM) have been performed on Vn96 mediated extracellular vesicle isolations of MCF-10A and MCF-7 cell culture media previously [7,26]. Both studies found particle size distributions consistent with small EVs.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently developed an EV capture method that uses a synthetic peptide called Vn96, which has binding affinity for heat shock proteins that are expressed in high abundance on the surface of EVs[7]. Vn96 is a small (27-mer) peptide, with an amino acid sequence of PSQGKGRGLSLSFRSWGALTLGEFLKL and a molecular weight of 2.9 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…Now, there are 3 confirmed ways to import exogenous proteins into exosomes [8488]. The first way is to use the transfection technique to load the exogenous proteins into exosomes directly [85, 86].…”
Section: Immunotherapy Strategymentioning
confidence: 99%
“…The glass substrates were further annealed at 560°C in order to modify the morphology from the multilayers of gold nanoparticles aggregates to nano-islands. In order to capture the exosomes, the affinity based synthetic polypeptide called Venceremin, Vn96 is used [6]. This molecule is specifically designed and validated to capture exosomes, having a strong affinity towards the canonical heat shock proteins (HSP), present on the surface of exosomes.…”
Section: Extended Abstractmentioning
confidence: 99%